Preparation, Characterisation and Antimicrobial Activities of Some Novel Nitriles and Imidazolines (Journal of Sciences, Islamic Republic of Iran)
Reaction between 5-methyl-3-aminoisoxazole and ?-acetamidophenylsulpho-nylchloride yielded compound 1. Hydrolysis of compound 1 gave a starting compound 4-methoxybenzal-?-5-methyl isoxazol-3-yl-sulphonamido aniline 2. The compound 2 on condensation with different aldehydes and potassium cyanide yielded the nitriles 3a-l. Cyclocondensation between oxazolinone and compound 2 yielded imidazolines 4a-l. All compounds have been characterised using IR, 1H NMR and Mass spectral data and have been evaluated for their antimicrobial activity against different strains of bacteria and fungi.